Introverts and Collaborative Learning - george jacobs (Master Program in Linguistics, Diponegoro University, 2014)
I was interested in reviewing Susan Cain’s (2013) “Quiet: The Power of Introverts in a World That Can’t Stop Talking” for two reasons. First, as an introvert I wanted to learn more about myself. Second, I wanted to explore Cain and others’ criticism that group activities in the workplace and in education are unfair to introverts. This book review contains two parts. The first part elaborates the general concept of introversion, borrowing heavily from the impressive amount of research and practical experience presented in Cain (2013). The second part addresses the criticism that teachers who use Cooperative Learning (CL) are being unfair to their introvert students. Saya tertarik untuk menelaah buku karya Susan Cain yang berjudul “Quiet: The Power of Introverts in a World That Can’t Stop Talking” karena dua alasan : pertama, sebagai seorang introvert saya ingin tahu lebih lanjut tentang diri saya; kedua, kritik tentang kegiatan kelompok dalam tempat kerja dan di tempat sekolah yang tidak fair bagi orang pendiam (introvert). Telaah buku ini berisi dua bagian. Bagian pertama mengelaborasi konsep umum tentang introversi, dengan mengacu ke sejumlah penelitian dan pengalaman praktis oleh Cain (2013). Bagian kedua, menelaah kritik tentang guru-guru yang menggunakan teknik “Cooperative Learning (CL)” itu tidak adil bagi siswa-siswa yang bersifat introvert atau pendiam.